2016
DOI: 10.1038/srep38836
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference: a promising biopesticide strategy against the African Sweetpotato Weevil Cylas brunneus

Abstract: The African sweetpotato weevil Cylas brunneus is one of the most devastating pests affecting the production of sweetpotatoes, an important staple food in Sub-Saharan Africa. Current available control methods against this coleopteran pest are limited. In this study, we analyzed the potential of RNA interference as a novel crop protection strategy against this insect pest. First, the C. brunneus transcriptome was sequenced and RNAi functionality was confirmed by successfully silencing the laccase2 gene. Next, 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…As observed in our study, suppression of Prosα2 and Snf7 transcript levels and significant mortality were reported in C. puncticollis and C. brunneus after oral delivery of dsRNA for the respective genes . In addition, we found that Snf7 dsRNA was the most lethal among the dsRNAs tested.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…As observed in our study, suppression of Prosα2 and Snf7 transcript levels and significant mortality were reported in C. puncticollis and C. brunneus after oral delivery of dsRNA for the respective genes . In addition, we found that Snf7 dsRNA was the most lethal among the dsRNAs tested.…”
Section: Discussionsupporting
confidence: 87%
“…As observed in our study, suppression of Pros 2 and Snf7 transcript levels and significant mortality were reported in C. puncticollis and C. brunneus after oral delivery of dsRNA for the respective genes. 29,30 In addition, we found that Snf7 dsRNA was the most lethal among the dsRNAs tested. This result is in agreement with a number of studies that have shown high mortality in several insect species exposed to Snf7 dsRNA, including Diabrotica virgifera virgifera, 36 Diabrotica undecimpunctata howardi, 37 Halyomorpha halys 38 and Amrasca biguttula biguttula.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In this context, the development of new methods for insect control is of key importance and there has been intense interest in the utility of gene silencing methods induced by RNA interference (RNAi). RNAi can induce mortality (Yang & Han, ; Cao et al., ; Abd El Halim et al., ; Christiaens et al., ; Hu et al., ; Malik et al., ), create beneficial phenotypes for insect control (Salvemini et al., ; Shukla & Palli, ; Peng et al., ; Yu et al., ), and prevent pesticide resistance in insect pests (Figueira‐Mansur et al., ; Guo et al., ; Wei et al., ; Bona et al., ; Sandoval‐Mojica & Scharf, ). Therefore, the potential for RNAi as a basis for future pest management strategies holds great promise (Huvenne & Smagghe, ; Gu & Knipple, ; Scott et al., ; Baum & Roberts, ; Kim et al., ).…”
Section: Rnai and The Sterile Insect Technique (Sit)mentioning
confidence: 99%